Perseverance counts but consistency does not! Validating the Short grit scale in a collectivist setting - Datu, Jesus Alfonso D. (Animo Repository, 2016)
The present research aims to validate the Short Grit Scale (Duckworth et al. Journal of Personality Assessment 91:166–174, 2009) among a sample of university (n = 220) and high school students (n = 606) from a collectivist culture (i.e., the Philippines) using both within-network and between-network approaches to construct validation. Our results revealed interesting cross-cultural differences in grit. First, grit was comprised of two distinct dimensions rather than as a hierarchical construct. Only the perseverance of effort dimension loaded onto the higher-order grit factor. Second, perseverance of effort was more salient in predicting key psychological outcomes (i.e., academic engagement and subjective well-being) compared to consistency of interests. This suggests that in collectivist cultures, the perseverance of effort dimension of grit is more relevant compared to the consistency of interest. Theoretical and practical implications are discussed. © 2015, Springer Science+Business Media New York.